2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591629
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound transducer positioning aid for fetal heart rate monitoring

Abstract: Abstract-Fetal heart rate (fHR) monitoring is usually performed by Doppler ultrasound (US) techniques. For reliable fHR measurements it is required that the fetal heart is located within the US beam. In clinical practice, clinicians palpate the maternal abdomen to identify the fetal presentation and then the US transducer is fixated on the maternal abdomen where the best fHR signal can be obtained. Finding the optimal transducer position is done by listening to the strength of the Doppler audio output and rely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Due to reciprocity, the same characterization applies to the US beam in receive mode. Using experiments and simulations, it was shown that transmission with multiple elements, positioned in a rigid gird, leads to an US beam profile with multiple side lobes and interferences [ 20 , 28 ]. It should be noted that a group of seven concentrically arranged transducer elements (e.g., elements with index i = 1, i = 3, i = 4, i = 6, i = 8 and i = 9 in Figure 1 b), corresponds to the array aperture of a commercially available US transducer [ 20 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Due to reciprocity, the same characterization applies to the US beam in receive mode. Using experiments and simulations, it was shown that transmission with multiple elements, positioned in a rigid gird, leads to an US beam profile with multiple side lobes and interferences [ 20 , 28 ]. It should be noted that a group of seven concentrically arranged transducer elements (e.g., elements with index i = 1, i = 3, i = 4, i = 6, i = 8 and i = 9 in Figure 1 b), corresponds to the array aperture of a commercially available US transducer [ 20 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Such transducer geometry is shown in Fig. 5(a), for which the corresponding generated US pressure field was generated The US waves transmitted by such US transducers interfere, leading to local variations in the US pressure within the medium [77]. The local pressure variations affect the amplitude of the reflected US echo, which is eventually received by the array.…”
Section: Monitoring Systemmentioning
confidence: 99%
“…This may be a tedious task and requires experienced clinicians. To support clinicians in positioning the US transducer, methods have been developed to estimate the fetal location [61], [62], [77]. These methods exploit a multi-element array and measure the Doppler power in each individual transducer element, which is then put into a probabilistic framework for fHL estimation.…”
Section: Monitoring Systemmentioning
confidence: 99%
See 2 more Smart Citations